A new non-iterative friction factor correlation for heat transfer fluids in absorber tube of parabolic trough collector - Utkucan Şahin (Engineering Science and Technology, an International Journal, 2018)
In this study, friction factors of heat transfer fluids (HTFs) that flow through the absorber tube in parabolic trough collector (PTC) are compared with using correlations. Syltherm 800 and Therminol VP-1 HTFs are considered for this study. Also, turbulent flow and rough pipe are considered for evaluation of the correlations of friction factor. The aim of this study is to compare a new non-iterative friction factor model, which is established for this study, with several alternative models against the Colebrook equation for friction factor and its effects on the relative error of pressure drop, Nusselt number estimated from the Gnielinski equation and heat transfer coefficient. All correlations are evaluated according to having mean absolute relative error (MARE) and root mean square error (RMSE). It is obtained that Reynolds number of Therminol VP-1 and Syltherm 800 are ranged from 1.1 × 104 to 2.97 × 106 and from 3.8 × 103 to 1.33 × 106, respectively. And, it is observed that friction factor of Syltherm 800 is higher than Therminol VP-1 at the same fluid temperatures. The results show that the new model established for this study is the closest correlation to the results of the Colebrook equation with having the lowest value of MARE and RMSE. MARE values of the new model is ranged in 0.01–0.02% for both Therminol VP-1 and Syltherm 800, and RMSE values of the new model are obtained as 3.78 × 10−6 and 5.57 × 10−6 for Therminol VP-1 and Syltherm 800, respectively.